Pemberdayaan Guru Sd Dalam Pengembangan Soal Hots Berbasis Ai Sebagai Strategi Mewujudkan Sdg 4 Pendidikan Berkualitas - Habibis Saleh; Ade Irma; Irma Fitri; Rena Revita (COMMUNITY SERVICE JOURNAL OF ECONOMICS EDUCATION, 2026)
Abstract  The primary challenge faced by teachers at UPT SD Negeri 008 Kualu is the limited time and competence in formulating evaluation instruments based on Higher Order Thinking Skills (HOTS). Teachers often struggle to design assessment items that effectively stimulate students' analytical, evaluative, and creative skills, particularly in mathematics. This community service program aims to enhance teachers' skills in developing HOTS-based mathematics evaluation instruments through the integration of Artificial Intelligence (AI) technology. The training was conducted by a community service team from the Mathematics Education Study Program at the State Islamic University of Sultan Syarif Kasim Riau, employing collaborative and interactive methods. Participants received practical guidance on utilizing AI applications, such as ChatGPT and Gemini, to design assessment items. The evaluation results indicated a significant increase in participants' competence. Prior to the training, 70.59% of participants reported an inability to compose high-level cognitive questions. However, after the training, over 80% were capable of independently constructing HOTS questions with AI assistance, and 99% demonstrated a clear understanding of AI integration techniques for evaluation instruments. This program demonstrates that AI can serve as a strategic partner in improving teacher efficiency and the quality of educational evaluation in elementary schools in accordance with SDG 4 goals. Keywords:  HOTS, Artificial Intelligence, Mathematics Evaluation, Teacher Training, ChatGPT